The Concept of Public Diplomacy in the 21st Century - Metushaj, Mirela (Acta Universitatis Danubius. Relationes Internationales, 2023)
This article provides a concise overview of the concept of public diplomacy, highlighting its key components and significance in contemporary international relations. Public diplomacy is a strategic communication and engagement concept employed by governments, organizations, and individuals to influence perceptions, build relationships, and achieve diplomatic objectives on the global stage. Unlike traditional diplomacy, which primarily focuses on interactions between governments, public diplomacy targets foreign publics, opinion leaders, and civil society organizations to shape narratives, foster understanding, and promote cooperation. The concept of public diplomacy underscores the importance of communication, engagement, and relationship-building in fostering cooperation, understanding, and goodwill between nations in an increasingly interconnected and complex global landscape.